The Urgency of Implementing Green Theology in Dealing with the Environmental Crisis - Yanuarius Azi, Paulus; Kaleka , Marten Umbu; Teftae , Oriensi Yakomina Kohe (Asian Journal of Environmental Research, 2025)
This study aims to analyze the current environmental crisis conditions, analyze the urgency of the Application of Green Theology in Overcoming the Environmental Crisis, Opportunities and Potential of Green Theology in Overcoming the Environmental Crisis. This study uses a qualitative research method with a literature study approach and textual analysis. The results of the study indicate that: 1) Indonesia's environmental conditions are concerning, serious efforts are needed to overcome them through public awareness, law enforcement, and environmentally friendly technology, with the concept of Ecological Repentance as one solution, 2) Green Theology is very important in overcoming the environmental crisis because it provides a holistic perspective on the relationship between humans and the environment. The implementation of Green Theology can help increase awareness and sustainable behavior, as well as promote environmental justice and interfaith cooperation. Thus, Green Theology can be a solution to overcome the environmental crisis and create a more sustainable future, and 3) Green Theology has great opportunities and potential in overcoming the environmental crisis by increasing awareness and sustainable behavior, as well as promoting environmental justice and cooperation between humans and nature. The implementation of Green Theology can be done through environmental education, sustainable lifestyles, and real actions to protect the environment, so as to reduce negative impacts on the environment and improve the quality of life.